The Impact of Perceived Organizational Justice, Psychological Contract, and the Burnout on Employee Performance: The Moderating Role of Organizational Support, in the Portuguese Context - Virgolino, Ana (2018)
Purpose: To identify the impact of perceived organizational justice (POJ), the psychological contract (PC), and burnout (BUR) on the employee’s individual performance (IP). The moderating role of perceived organizational support (POS) is analysed. Methodology: The study uses a structured questionnaire to gather data from a cross–sectional sample of 407 employees. Structural Equation Modelling (SEM) is used to test the proposed hypotheses, and a multi-group analysis is conducted to find how the perception of the PCV can impact on the suggested relationships. Findings: POJ has a positive impact on the PC and on IP. However, the impact of the PC and the first two dimensions of BUR on IP are not significant. POS moderates some of the suggested relationships. Implications: contributes to the knowledge about the combined impact of POJ, the PC and BUR, introducing the role of POS as a moderating variable in the relationships between organizations and employees. The global results may inform strategies to secure positive human resource management (HRM) outcomes. Originality: This research is original in order these concepts and relationships of mediation and moderation are presented in a single study providing a model that depicts a chain of important effects.